STIMULATING AND LIMITING MEANS OF FORMATION AND REALIZATION OF LAW ENFORCEMENT POLICY - Margarita Hamletovna Arutjunova (Современная наука и инновации, 2022)
The article examines the theoretical and practical combination problems of stimulating and limiting means of law enforcement policy formation and realization; analyses different points of view about effective ways of public development management in the framework of the law enforcement policy; conclusions and suggestions are made regarding the role of stimulating and limiting means of formation and realization of policy enforcement.